Intermodal transportation costs - Hämäläinen Esa; Inkinen Tommi (Slovenia, 2022)
This paper reveals with empirical case data how the maritime-based short sea shipping costs aggregate in export industry. The authors had the possibility to utilize invoice data of the delivered orders. The data contains the information of logistics costs from the mill located in a Nordic country to two customers located in two different countries in the Mediterranean region. This study shows that micro level data may reveal interesting perspectives of the logistics costs research tradition.
Keywords: intermodal transport, logistics cost, export industry
Proceedings of 18th International Conference on Transport Science